(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The research concerned the biggest, the deepest and the youngest (25 years old) acidotrophic reservoir located 4 km south-east from Lqknica. It was created as a result of brown-coal mining and opencast method. The present pyrite was the cause of significant acidifying and salinity of waters. 17 years of physico-chemical examinations of waters showed a progressive difference between mixo- and monimolimnion that is increase or decrease of such indicators as pH, redox potential, total iron, sulphate and others. First symptoms of ageing o f the reservoir were visible. Biological examinations showed pancity of plant and animal species living in this reservoir and a very slow development ofbiocoenosis. The research concerned the biggest, the deepest and the youngest (25 years old) acidotrophic reservoir located 4 km south-east from Lqknica. It was created as a result of brown-coal mining and opencast method. The present pyrite was the cause for significant acidifying and salinity of waters. 17 years of physico-chemical examinations of waters showed a progressive difference between mixo- and monimolimnion that is increase or decrease o f such indicators as pH, redox potential, total iron, sulphate and others. First symptoms of ageing o f the reservoir were visible. Biological examinations showed pancity of plant and animal species living in this reservoir and a very slow development of biocoenosis.